2018
DOI: 10.1111/jvp.12509
|View full text |Cite
|
Sign up to set email alerts
|

Stable gastric pentadecapeptide BPC 157 in honeybee (Apis mellifera) therapy, to control Nosema ceranae invasions in apiary conditions

Abstract: Nosema ceranae can cause major problems, such as immune suppression, gut epithelial cell degeneration, reduced honeybee lifespan, or suddenly colony collapse. As a novel approach in therapy, we hypothesize the stable gastric pentadecapeptide BPC 157 in honeybee therapy, to control N. ceranae invasions in apiary conditions: BPC 157 treated sugar syrup (0.25 L sugar syrup supplemented with 0.1 μg/ml BPC 157), as well as the pure sugar syrup (0.25 L sugar syrup; control), was administered to honeybee colonies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
(100 reference statements)
2
32
0
1
Order By: Relevance
“…But more important is the practical indicative evidence that even with the majority of studies on BPC 157 done on rodents given injection of the supplement, there are considerable number of the studies, particularly in gastrointestinal research, intragastric application or per-oral application in drinking water, correspondingly effective. 12,41,43,48,51,54,55,58,59,[61][62][63][82][83][84][85]89,[91][92][93]98,114,116,117,[143][144][145][146][147][149][150][151][152][153][154][155] In reality, in particular along with its safe profile, LD-1 not achieved, and no adverse effects in clinical trials, [1][2][3][4][5][6][7][8][9][10][11]…”
Section: Discussionmentioning
confidence: 99%
“…But more important is the practical indicative evidence that even with the majority of studies on BPC 157 done on rodents given injection of the supplement, there are considerable number of the studies, particularly in gastrointestinal research, intragastric application or per-oral application in drinking water, correspondingly effective. 12,41,43,48,51,54,55,58,59,[61][62][63][82][83][84][85]89,[91][92][93]98,114,116,117,[143][144][145][146][147][149][150][151][152][153][154][155] In reality, in particular along with its safe profile, LD-1 not achieved, and no adverse effects in clinical trials, [1][2][3][4][5][6][7][8][9][10][11]…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported about the first appliance of stable gastric pentadecapeptide BPC 157 to honeybee colonies with achieved significant therapeutic effects against Nosemosis type C [ 1 ], caused by microsporidium Nosema ceranae [ 2 ]. We hypothesized and confirmed that BPC 157, as a new way of honeybee therapy, can be used to counteract N. ceranae invasions in field conditions and increase colonies strength [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, considering the presented and previous findings in fistula research [5][6][7][8][9][10], this study should overwhelm the general point that animal studies per se may be cautious, and fistulas studies; in particular, regarding their results and the relative paucity of the BPC 157 clinical data [1][2][3][4]. On the other hand, BPC 157 was proved to be efficacious in the ulcerative colitis, both in clinical settings [65,66], and in the experimental rats studies, in the ischemic/reperfusion vascular ulcerative colitis studies [60] and other ulcerative colitis models, induced by TNBS [67], cysteamine, surgery [31,68,69], NSAIDs [30,[70][71][72][73], or major vessel occlusion [48][49][50][51][52]59], including various species [74], and fistulas as complications (for review see, i.e., [3]). A particular point for revealing and applying this concept in practice (BPC 157's beneficial effect on various fistulas toward counteraction of the vesicovaginal fistulas in particular) is a very safe profile (LD1 could be not achieved) [17], a point recently confirmed in a large study of the Xu and collaborators [75].…”
Section: Discussionmentioning
confidence: 99%